Human milk microbial species are associated with mild growth deficits during early infancy among Guatemalan mother–infant dyads - Ajeeb, Tamara T.; Gonzalez, Emmanuel; Solomons, Noel W.; Koski, Kristine G. (Frontiers in Microbiomes, 2022)
Growth faltering is common in Guatemalan indigenous communities, but the possibility that it may be related to milk microbial composition has not been explored. For this cross-sectional study, unrelated mother–infant dyads (n = 64) from eight communities in the remote Western Highlands of Guatemala were recruited. Milk samples and infant length-for-age and weight-for-age Z-scores were collected at two stages of lactation: early (6–46 days postpartum, n = 29) or late (109–184 days postpartum, n = 35). Within each stage of lactation, infants were subdivided into mildly underweight [weight-for-age Z-score (WAZ) < –1 SD] or normal weight (WAZ ≥ –1 SD) and mildly stunted [length-for-age Z-score (LAZ) < –1.5 SD] or non-stunted (LAZ ≥ –1.5 SD). 16S ribosomal RNA gene sequencing was used to identify milk microbial communities, and DESeq2 was used to compare the differential abundance (DA) of human milk microbiota at the species level for WAZ and LAZ subgroups at each stage of lactation. A total of 503 ESVs annotated as 256 putative species across the 64 human milk samples were identified. Alpha diversity did not differ, but beta-diversity redundancy analysis identified four distinct clusters among the four WAZ (p = 0.004) and LAZ subgroups (p = 0.001). DA identified 15 different taxa in the WAZ and 11 in the LAZ groups in early lactation and 8 in the WAZ and 19 in the LAZ groups in late lactation. Mothers’ milk had more DA taxa of oropharyngeal and environmental bacteria with opportunistic activities in the LAZ < –1.5 SD infants, whereas the LAZ ≥ –1.5 SD had DA taxa with potential probiotic and antimicrobial inhibitory activity against pathogens. In particular, milk microbial communities of infants not classified as underweight or stunted had more beneficial species including Lactococcus_lactis. These findings suggest the potential associations between the milk microbiome at the species level with infant growth prior to 6 months of age. These data provide important evidence of the associations between the human milk microbiome and the growth of breastfed infants.